Effect of concurrent training on physical performance and quality of life in children with malignancy: A systematic review and meta-analysis - Zang, Wanli; Fang, Mingqing; Chen, Haohao; Huang, Xinmeng; Li, Dong; Yan, Jin; Shu, Heng; Zhao, Mingyuan (Frontiers in Public Health, 2023)
Objective: This study aims to evaluate the intervention effect of concurrent training on children with malignant tumors to provide evidence for prescribing exercise for children with malignant tumors. Methods: Twelve databases were searched from inception to October 15, 2022. Two researchers independently screened the literature, evaluated the quality, extracted the data, and performed the meta-analysis using R. Result: A total of nine randomized controlled trials involving 371 children were included in this study. The meta-analysis revealed that muscle strength was significantly greater in the exercise group compared to the usual care group [SMD=0.26, 95% CI (0.04, 0.48), P=0.023], with subgroup analysis showing no significant difference in upper limb [SMD=0.13, 95% CI (-0.17, 0.43), P=0.318] and a considerable difference in lower limb strength [SMD=0.41, 95% CI (0.08, 0.74), P=0.015]. Physical activity [SMD=0.57, 95% CI (0.03, 1.1), P=0.038], timed up and down stairs test [SMD=-1.22, 95% CI (-2.04, -0.4), P=0.004], walkability [SMD= 0.75, 95% CI (0.38, 1.11), P<0.01], quality of life [SMD=0.28, 95% CI (0.02, 0.53), P=0.033], and cancer-related fatigue [SMD=-0.53, 95% CI (-0.86, -0.19), P=0.002] were significantly better than the usual care group. There were no significant differences in peak oxygen uptake [SMD=0.13, 95% CI (-0.18, 0.44), P=0.397], depression [SMD=0.06, 95% CI (-0.38, 0.5), P=0.791] and withdrawal rates [RR=0.59, 95% CI (0.21, 1.63), P=0.308] between the two groups. Conclusion: Concurrent training was effective in enhancing motor performance for children with malignancy but had no significant effect on mental health. Future high-quality randomized controlled trials are required to confirm these findings.